A multi‐tracer approach to quantifying groundwater inflows to an upland river; assessing the influence of variable groundwater chemistry. Issue 1 (13th December 2013) - Atkinson, A. P.; Cartwright, I.; Gilfedder, B. S.; Hofmann, H.; Unland, N. P.; Cendón, D. I.; Chisari, R.
Abstract Understanding the behaviour and variability of environmental tracers is important for their use in estimating groundwater discharge to rivers. This study utilizes a multi‐tracer approach to quantify groundwater discharge into a 27 km upland reach of the Gellibrand River in southwest Victoria, Australia. Ten sampling campaigns were conducted between March 2011 and June 2012, and the distribution of 222Rn activities, Cl and 3H concentrations imply the river receives substantial groundwater inflows. Mass balances based on 222Rn, Cl and 3H yield estimates of groundwater inflows that agree to within ± 12%, with cumulative inflows in individual campaigns ranging from 24 346 to 88 467 m3/day along the studied river section. Groundwater discharge accounts for between 10 and 50% of river flow dependent on the time of year, with a high proportion (>40 %) of groundwater sustaining summer flows. Groundwater inflow is largely governed by regional groundwater flowpaths; between 50 and 90% of total groundwater inflows occur along a narrow 5–10 km section where the river intersects the Eastern View Formation, a major regional aquifer. Groundwater 222Rn activities over the 16 month period were spatially heterogeneous across the catchment, ranging between 2000 Bq/m3 and 16 175 Bq/m3. Although groundwater 222Rn activities display temporal variation, spatial variation in groundwater 222Rn is a key control on 222Rn mass balances in river catchments where groundwater and river 222Rn activities are within an order of magnitude of each other. Calculated groundwater discharges vary from 8.4 to 15 m3/m/day when groundwater 222Rn activities are varied by ± 1 σ. Copyright © 2013 John Wiley & Sons, Ltd.